Evaluating the Impact of Practical Training: A Study on Satisfaction and Drug Knowledge among Pharmacy Students - Nobuyuki Wakui; Shunsuke Shirozu; Yoshiaki Machida (MDPI AG, 2024)
Practical training stands as a crucial component in shaping pharmacy students, bridging the gap between classroom-based theoretical knowledge and its application in real-world contexts. This study investigates the correlation between the satisfaction levels experienced during practical training and the acquisition of knowledge, particularly focusing on drug names. Drawing from the National DataBase (NDB) open data provided by Japan's Ministry of Health, Labour and Welfare, a survey centered on the top 100 dispensed drugs was crafted. A correlation analysis was conducted between the satisfaction scores gathered from students and their depth of knowledge on drug names. Intriguingly, despite observing a significantly high satisfaction level during the practical training, there was no marked correlation between this satisfaction and the proficiency in recalling drug names after the training. Furthermore, the volume of daily prescriptions handled did not significantly impact this knowledge. The findings underscore the notion that high satisfaction during training does not necessarily guarantee a thorough understanding of the subject matter. This sheds light on the importance of not solely relying on satisfaction metrics in training programs and ensuring a holistic, in-depth educational approach.